Reoviruses I : Structure, Proteins, and Genetics - Tyler, Kenneth L. (Current topics in microbiology and immunology, 1998)
Reoviruses are one of the most important viral groups for understanding the molecular and genetic basis for viral pathogenesis. These two volumes cover virtually all aspects of reovirus biology. Volume I begins with a review of reovirus structure; further chapters deal with functions of the reovirus structural proteins, the assembly of the genome, and reovirus mutants. Volume II reviews general mechanisms of reovirus persistent infection and cytopathic effects, and then discusses reovirus-induced disease in specific organ systems including the heart, nervous and endocrine systems, liver and biliary system, and intestine. Together, these two volumes provide a current and comprehensive review of the mammalian reoviruses.